2012
DOI: 10.1093/europace/eur412
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of left ventricular pacing vector programmability in cardiac resynchronization therapy defibrillator patients for management of phrenic nerve stimulation and/or elevated left ventricular pacing thresholds: insights from the Efface Phrenic Stim study

Abstract: The programmability of LV pacing vectors is a powerful feature to avoid PNS and obtain acceptable LV pacing thresholds. In order to retain reprogramming options for LV vectors during FU, LV pacing leads with at least two electrodes should be chosen whenever possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 26 publications
1
12
0
1
Order By: Relevance
“…This result is in the range of previously reported rates of PNS with bipolar leads, ranging from 1% [16] to 13% [17]. Therefore, bipolar leads remain a reliable and World Journal of Cardiovascular Diseases suitable alternative in patients whose anatomy prevents multiple electrode implantation.…”
Section: Discussionsupporting
confidence: 72%
“…This result is in the range of previously reported rates of PNS with bipolar leads, ranging from 1% [16] to 13% [17]. Therefore, bipolar leads remain a reliable and World Journal of Cardiovascular Diseases suitable alternative in patients whose anatomy prevents multiple electrode implantation.…”
Section: Discussionsupporting
confidence: 72%
“…Improvements in lead design and delivery tools led to a transvenous approach into a venous tributary of the coronary sinus, thus eliminating the morbidity and complexity inherent to epicardial LV lead implantation . However, these leads needed to be wedged into branch vessels for lead stability; as a result, electronic repositioning had limited success in eliminating PNS . Initial CRT clinical studies were all performed with unipolar or bipolar leads with these limitations .…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that up to 5% of all patients with CRT devices undergo repeat surgery for PNS, and at least 1–2% have their LV lead deactivated due to PNS . Electronic reprogramming has been an important tool to minimize PNS without compromising the efficacy of CRT . Ideally, a given LV pacing configuration should have a low LV threshold without PNS and/or large PN threshold–LV threshold difference to allow program pacing output at twice LV threshold (ideal 100% LV capture safety margin).…”
Section: Discussionmentioning
confidence: 99%
“…Two studies reported that Ring→RV coil and Tip→Ring had a significantly higher PN voltage threshold compared to Tip→RV coil . These studies included devices with only 3 available pacing configurations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation